Power, Predistribution, and Social Justice. (13th November 2019) - O'Neill, Martin
Abstract: The idea of predistribution has the potential to offer a valuable and distinctive approach to political philosophers, political scientists, and economists, in thinking about social justice and the creation of more egalitarian economies. It is also an idea that has drawn the interest of politicians of the left and centre-left, promising an alternative to traditional forms of social democracy. But the idea of predistribution is not well understood, and stands in need of elucidation. This article explores ways of drawing the conceptual and normative distinction between predistribution and redistribution, examining those general categories when considering the roles of public services and fiscal transfers, and looking at the ways in which government policies can empower and disempower different individuals and groups within the economy. This article argues that the most initially plausible and common-sensical ways of drawing the distinction between predistributive and redistributive public policies collapse when put under analytical pressure. It concludes that the distinction between predistribution and redistribution is best seen in terms of the aims or effects of policies rather than a deeper division of policy types, and argues that, once seen in those terms, predistribution is a central concern of social justice.